Effect of covid-19 on human resource management: evidence from the apparel industry - Mathushan, P.; Kengatharan, N.; Saravanabawan, A. (South Eastern University of Sri Lanka, 2022)
Owing to the persistent changes in the business climate, firms are progressively looking at their human resources (HRs) as a crucial resource that can help with harvesting competitive advantage. HRs are considered by numerous individuals to be the main resource of a firm for sustaining competitiveness. Drastic transformations brought about by COVID-19 have affected human resources significantly in many ways. Therefore, the study aims to explore the effect of COVID-19 on human resource management. Using a purposive sampling technique, the data were marshaled from Managers, HR managers, and executives working in the apparel industry. The findings demonstrate that organizations, along with the HR supervisors, must formulate precautionary countermeasures, rethink, and reform new HR strategies concerning their human resources for distant just as blended working frameworks as a reaction to current and future emergencies. Employees also require training and development interventions to reinforce their capability to concur the unprecedented situations. Firms have to reimagine and reform their jobs to improve productivity. Additionally, COVID‐19 has changed the experience of work for by far most employees.
Keywords: COVID-19; Competitive advantage; Human resource management; Business environment; Competitiveness